O "Massacre de Nanking" e a violência de gênero contra as mulheres, China (1937-1938) - Silva, Altino Silveira (2011)
The Second World War in the campaign of the Pacific Ocean comprehends two different, but interweaved, armed conflicts which lasted over a span of eight years. They are the Second Sino-Japanese War (1937-1945) and Pacific War (1941-1945), which can be considered only one conflict, or as phases of the same path. Of all the locations sitting atop the Yangtze River delta, where the main battles among the Chinese and Japanese were fought during the conflict, in the city of Nanking was place of a massacre of enormous proportions. This episode came to be known as the “Nanking Massacre”, and during the eight weeks that followed the day December 13, 1937. This event summarizes the violence committed by the Japanese military during the whole war. The estimates are that over 200,000 people were murdered and 20,000 women were raped. In an attempt to contribute towards a better understanding of the subject, the present research aims to offer an approach that focused its attention on gender-based violence, especially that of a sexual nature, suffered by Chinese women, carried out by Japanese soldiers in the firsts 67 days of occupation. We intend to interpret the sexual abuse that victimized as an action greatly due to the asymmetries of power between the male and female gender. These asymmetries were based on values, prejudices and social practices which established an unequal relationship between men and women, putting the latter in a situation of debility and submission in face of the men. The ideological aspect was intensified by the situation of social frailty and dereliction due to the bankruptcy of the control and repression apparatus. In order to do so, we will work historical and cultural aspects from Japan and China, which possessed a correlation with gender issues. We intent to provide information about the cases of violence perpetrated during the “Nanking Massacre”, a quantitative study was developed from the recountings found in diaries and pieces of correspondence belonging to the foreigners who resided in the city. The perusal of the notes has turned the stories into data, and out of their inspection it was possible do decipher the specificities of the violence committed, producing statistics and developing case descriptions and their distribution in time and space.